Canonical jurisprudence in the kingdom of bohemia in the Middle Ages - Krafl Pavel (Anali Pravnog Fakulteta u Beogradu, 2023)
During the High and Late Middle Ages, canon law played a crucial role. This study provides an overview of ecclesiastical legal scholarship in the Czech lands, i.e. in Bohemia (in the Archdiocese of Prague) and in Moravia (in the Diocese of Olomouc). The development of a legal jurisprudence went hand in hand with the development of ecclesiastical administration in the second half of the 14th century and in the early 15th century, which evolved into a compact system. An important factor in this was the establishment of Prague University, including the Law Faculty, in 1348, and also, in particular, the establishment of the separate Prague Law University in 1372. Amongst the major canonists who left work behind were Štěpán of Roudnice, Bohuslav of Krnov, Kuneš of Třebovle, Mikuláš Puchník, and Jan of Jesenice, amongst others.